Design of an incentive mechanism to promote honesty in e-marketplaces with limited inventory - Liu, Yuan (2013)
In e-marketplaces with limited inventory where buyers' demand is larger than sellers' supply, promoting honesty raises new challenges: sellers may behave dishonestly because they can sell out all products without the necessity of gaining high reputation; buyers may provide untruthful ratings to mislead other buyers in order to have a higher chance to obtain the limited products. In this paper, we propose a novel incentive mechanism to promote honesty in such e-marketplaces. More specifically, our mechanism models both buyer and seller honesty. It offers higher prices to the products provided by honest sellers so that the sellers can gain more profit. Honest buyers also have a higher chance to do business with honest sellers and are able to gain more utility. Theoretical analysis and experimental results show that our mechanism promotes both buyer and seller honesty. Finally, we address the re-entry problem by imposing membership fees on new sellers. We show that the membership fee can discourage sellers from re-entry both in theoretical analysis and experimental validation.